2022
DOI: 10.1136/bmjgh-2021-008268
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to evidence-informed decision-making in the context of pandemics: qualitative study of COVID-19 policy advisor perspectives

Abstract: IntroductionThe exceptional production of research evidence during the COVID-19 pandemic required deployment of scientists to act in advisory roles to aid policy-makers in making evidence-informed decisions. The unprecedented breadth, scale and duration of the pandemic provides an opportunity to understand how science advisors experience and mitigate challenges associated with insufficient, evolving and/or conflicting evidence to inform public health decision-making.ObjectivesTo explore critically the challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…While all youth in this study agreed that science plays a critical role in public health preparedness, a qualitative study of COVID-19 policy advisors reported the challenges that scienti c advisors experienced over the COVID-19 period. (57) These challenges included the inability to stay up-to-date on the evidence given the overwhelming, rapid generation of evolving and sometimes con icting evidence; scienti c uncertainty about different pandemic-related scenarios; the misinterpretation and misapplication of evidence; concerns about research integrity; and the lack of clarity on the integration of multi-sectoral evidence. At the same time, scienti c advisors reported that they experienced a lack of transparency with governmental decision-makers on how pandemic-related decisions were made (57).…”
Section: Discussionmentioning
confidence: 99%
“…While all youth in this study agreed that science plays a critical role in public health preparedness, a qualitative study of COVID-19 policy advisors reported the challenges that scienti c advisors experienced over the COVID-19 period. (57) These challenges included the inability to stay up-to-date on the evidence given the overwhelming, rapid generation of evolving and sometimes con icting evidence; scienti c uncertainty about different pandemic-related scenarios; the misinterpretation and misapplication of evidence; concerns about research integrity; and the lack of clarity on the integration of multi-sectoral evidence. At the same time, scienti c advisors reported that they experienced a lack of transparency with governmental decision-makers on how pandemic-related decisions were made (57).…”
Section: Discussionmentioning
confidence: 99%
“…Trust plays a particularly critical role when decisions are made in contexts of uncertainty. Uncertainty, of course, is a central feature of most clinical decision making, particularly for conditions (e.g., COVID-19 30 ) or treatments (e.g., deep brain stimulation 31 or gene therapies 32 ) that lack a long history of observed outcomes. As Wang and Busemeyer (2021) 33 describe, "uncertain" choice situations can be distinguished from "risky" ones in that risky decisions have a range of outcomes with known odds or probabilities.…”
Section: Impacts Of Uncertainty and Urgency On Decision Qualitymentioning
confidence: 99%
“…Similar requirements have been suggested in other jurisdictions, yet the pandemic revealed a lack of transparency even where decisions affected an entire population, often for prolonged periods of time. Many jurisdictions also appear to lack a standardised mechanism for making relevant conflicts of interest among health officials a matter of the public record.There is thus an opportunity to develop more transparent and accountable processes for evidence-informed decision-making during pandemics and other public health crises(Vickery, Atkinson et al 2022 ).…”
Section: Transparencymentioning
confidence: 99%